Plasma Treatment and TEOS Modification on Wood Flour Applied to Composite of Polyvinyl Chloride/Wood Flour - Trung H. Tran; Hoang Thai; Huynh D. Mai; Hung Q. Dao; Giang V. Nguyen (Advances in Polymer Technology)
In this work, the effects of wood flour and tetraethyl orthosilicate (TEOS) content on the fusion time, fusion torque, fusion temperature, and fusion energy of polyvinyl chloride/wood flour (PVC/WF) composites were studied. Plasma-assisted surface treatment of WF before modifying with TEOS to form the silica nanoparticles on the surface of wood flour plays a role as a reinforcement of the phase interaction. This modification was confirmed by X-ray photoelectron spectroscopy (XPS) and field emission scanning electron microscopy (FESEM) techniques. Moreover, BET data showed that specific surface area and volume of plasma treated WF and TEOS modified WF (WS) were considerably improved in comparison with original WF. By increasing WF, a remarkable increase in time, temperature, and energy of mixing process led to the enhancement of fusion torque. In the case of composite using WS, the increase of TEOS content resulted in shorter fusion time, whereas the other fusion characteristics of composites increased. The investigation of mechanical and rheological properties such as Young’s modulus and dynamic storage modulus G′ showed the stiffness of the PVC/WF composites has been significantly improved with increasing wood flour and modifier contents. The research showed an application of nanoparticles in the industrial production of polymer composite materials.